Study of D0→π-e+νe, D+→π0e+νe, D0→K-e+νe, and D+→K̄0e+νe in tagged decays of the ψ(3770) resonance - Ge, J; Miller, D; Pavlunin, V; Sanghi, B; Shipsey, I; Xin, B; Adams, G; Hu, D; Moziak, B; Napolitano, J; Ecklund, K; He, Q; et al. (2009)
Using ψ(3770)→DD̄ events collected with the CLEO-c detector at the Cornell e+e- storage ring, tagged by fully reconstructing one D meson in a hadronic decay mode, we measure absolute branching fractions and differential decay rates for D0→π-e+νe, D+→π0e+νe, D0→K-e+νe, and D+→K̄0e+νe. The measured decay rates are used to study semileptonic form factors governing these transitions and to test unquenched Lattice QCD (LQCD) calculations. We average our results with previously published CLEO-c measurements of the same quantities using a neutrino reconstruction technique. Combining LQCD calculations of form factor absolute normalizations f+(0) and measurements of f+π(0)|Vcd| and f+K(0)|Vcs|, we find |Vcd|=0.222(8)(3)(23) and |Vcs|=1.018(10)(8)(106), where the uncertainties are statistical, experimental systematic, and from LQCD, respectively. © 2009 The American Physical Society.